IDENTIFICATION OF ANTHROPOGENIC FEATURES THROUGH APPLICATION OF PRINCIPAL COMPONENT ANALYSIS TO HYDROCHEMICAL DATA FROM THE SINES COASTAL AQUIFER, SW PORTUGAL - Fernandes P.G.; Carreira P.; Da silva M.O. (My University, 2006)
The Sines coastal sedimentary basin, a tectonic trough with a NE-SW orientation filled with Mesozoic and Cenozoic deposits, has two hydrogeological systems: the Mio-Pliocene and the Jurassic. Both systems are supplying water to the entire region with highly populated and industrialized areas. The aquifers are recharged in the outcrop areas, although the Jurassic aquifer also receives some contribution from the overlying Miocene rocks. The main groundwater flow direction in the Jurassic aquifer is E to W towards the Atlantic Ocean. In order to understand the influence of anthropogenic activities on the water quality, a statistical principal components analysis (PCA) was performed on the physical–chemical data from groundwater samples in both aquifers. Four components were obtained in the Jurassic and three in the Miocene. The principal components analyses indicate water–rock interactions as the major mechanism responsible for the groundwater solutes (mainly calcium-bicarbonate type), from the calcareous and dolomitic units. Anthropogenic contamination was identified in the influence of the water compositions, corresponding to local polluting inputs. These were magnesium, sulfate, nitrate, iron and copper for PC 3 in the Jurassic and sodium, chloride, nitrate and manganese for PC 2 in the Miocene. These account for about 13% of the system total variance in the Jurassic aquifer and near 23% in the Miocene one.
Keywords: PRINCIPAL COMPONENT ANALYSIS; GROUNDWATER EVOLUTION; SINES COASTAL AQUIFER; Jurassic; Pliocene; Miocene; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен